Mikro-Simulasi Prasarana U-Turn Menggunakan Sofware VISSIM Pada Ruas Jalan Teuku Nyak Arief Kota Banda Aceh - Cut Nawalul Azka; Hidayat, Rifki; Aldi Fajri (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Heavy traffic conditions for road users, especially on Teuku Nyak Arief Street, Banda Aceh City at U-turn often cause high traffic disruption, where it is difficult to understand road conditions, because the position of the U-turn is often found to be ineffective, including less than ideal road conditions with the presence of roads so congested that it will affect U-turns and congestion at active U-turns. The problem is how to improve the effectiveness of U-turns through microsimulation of the VISSIM software against the model scenario. The method used is to analyse the level of service using VISSIM software on the delay value. Based on the analysis of existing, there is a poor LOS U-turn 4 which is LOS E with a delay value of 41.79 vehicles/second, but there is also a U-turn whose level is quite good such as U-turn 1 with 24.17 vehicles/second. Recommendation at U-turn 4 to improve road service by closing the north-south road and diverting to U-turn 3. U-turn 4, which was originally a double U-turn, has been changed to a single U-turn (for north-south U-turns only). The best advice given is traffic management with consideration based on local conditions.